(untitled) (Bangladesh Journal of Psychology, 2026)
Cognitive impairment (CI) is an age-related illness involving declines in memory, attention, and executive functioning, adversely affecting well-being and increasing the chances of dementia. An accurate assessment of CI in Bangladesh needs culturally suitable screening tools, as many existing tools were developed in Western contexts. So, valid, reliable, and culturally appropriate screening tools are urgently needed to detect CI early. The study aimed to adapt and validate the 6-item Cognitive Impairment Test (6-CIT) in Bangla for use among older adults. Using a cross-sectional design, data were collected via convenience sampling from 681 older adults aged 60 to 79 years in Bangladesh. Psychometric assessment showed strong item quality, as indicated by item-total and inter-item correlations. Internal consistency and test-retest reliability were excellent, as indicated by McDonald’s omega (ω), Cronbach’s alpha (α), and Guttman lambda (λ2). Expected differences across age, gender, smoking habit, and sleeping pill use confirmed known-group validity. Correlations with stress and well being showed evidence of convergent and divergent validity. Velicer’s MAP test showed a unidimensional structure for the scale, while EFA confirmed the adequacy of the data (KMO =.77; Bartlett’s X2 =1628.59, p <.001). The initial two-component solution explained 72.68% of the variance. The receiver operating characteristic analysis showed good to excellent item accuracy. Overall, the Bangla 6-CIT is a reliable, valid, and feasible screening tool for primary care and community-based settings to support early detection and intervention for CI of older adults in Bangladesh. Bangladesh Journal of Psychology, Vol. 26(1), June 2026, pp. 41-60